Synopsis of the genus Eldarca Signoret, 1864 (Hemiptera: Heteroptera: Coreidae) - Faúndez, Eduardo I. (Zootaxa, 2015)
A synopsis of the Coreid genus Eldarca Signoret, 1864 is presented. Full species status is given to Eldarca rufa Reed, 1899 n. stat. New distributional data are provided for Eldarca nigra Signoret, 1864. Eldarca haematoloma rufa Reed, 1899 n. stat. is considered as subspecies of E. haematomera. Eldarca nigroscutellata sp. nov. is described from southern Patagonia; which becomes also the southernmost record of Coreidae in South America. Differential diagnoses and figures for all the species of the genus are included. The distribution of the species is commented and a distribution map is provided. A key to the four known species of Eldarca is added.